Case report: pathological complete response in an IIIB non-small cell lung cancer patient after preoperative neoadjuvant nivolumab therapy combined with chemotherapy - Luzhen Li, MM; Ting Chen, MM; Huiqin Lai, BD; Ao Zhang, BD; Xianhui Zhao, MM; Jiaming Wu, MM; Huisi Hong; Lexia Wu, BD; Sihong Lin, BD; Kexin Wang, LP; Huatang Zhang, BD; Cantu Fang, BD (Medicine, 2022)
Abstract. Rationale:. For locally advanced non-small cell lung cancer (NSCLC), the neoadjuvant therapy strategy of preoperative nivolumab combined with chemotherapy has great potential, especially for locally advanced NSCLC which are initially unresectable. They may be cured after neoadjuvant immunotherapy, and this may become a new direction of treatment. We hope that this representative medical record and literature review can provide some assistance for clinicians using immune checkpoint inhibitors to treat lung cancer. Patient concerns:. A 50-year-old male patient was admitted to Zhongshan Hospital of Traditional Chinese Medicine on April 27, 2020 due to “coughing for more than one month.”. The patient had nothing of note in either his medical history or that of his family, and no history of smoking. Diagnosis:. The diagnosis was cT4N2M0IIIB stage right lower lung NSCLC with right hilar and mediastinal lymph node metastasis. The stage was inoperable stage IIIB NSCLC, but the patient had a strong willingness for doing surgery. Interventions:. The patient received 3 rounds of the neoadjuvant nivolumab therapy combined with TP (paclitaxel plus cisplatin) regimen, on 5-14-21, 06-07-21 and 07-07-21. Outcomes:. The tumor's area shrunk. Then the patient underwent thoracoscopic radical resection of the cancer in the right upper lung and postoperative pathology achieved pathological complete response (pCR) Lessons:. In this case, combined with the wishes of the patient and the latest research results, we confirmed pCR by radical surgery after 3 rounds of the neoadjuvant nivolumab therapy combined with chemotherapy. This may be a modality to cure more lung cancer patients in the future.